Alcohol reform – New Zealand style: Reflections on the process from 1984 to 2012. (February 2017) - Sellman, Doug; Connor, Jennie; Robinson, Geoffrey; McBride, Sam
Abstract: This paper traces 30 years of alcohol reform in New Zealand, from the early 1980s through to the passing of the Alcohol Reform Bill in 2012. It begins with the liberalisation of alcohol through the passing of the Sale of Alcohol Act in 1989 allowing wine to be sold in supermarkets, followed by beer in 1999 along with a reduction in the age of purchase of alcohol from 20 to 18 years. Soon after a South Auckland shooting of a liquor store owner in 2008, the government announced a major review of the alcohol laws to be conducted by the New Zealand Law Commission. The remainder of the paper outlines the process by which successive National‐led governments carefully managed this review and finally passed an Alcohol Reform Bill which contained very little in the way of reform. The paper documents how the government engaged in a drawn‐out process with significant time delays, largely ignoring the main evidence‐based recommendations of the Law Commission, withholding vital information from the public, dismissing concerns expressed by both the public and opposition parties, and using a combination of the "conscience vote" and an unusual voting procedure in Parliament to deliver a Bill that was favourable to the alcohol industry.